Postanastomotic Transplant Renal Artery Stenosis: Association With De Novo Class II Donor‐Specific Antibodies. Issue 1 (January 2014) - Willicombe, M.; Sandhu, B.; Brookes, P.; Gedroyc, W.; Hakim, N.; Hamady, M.; Hill, P.; McLean, A. G.; Moser, S.; Papalois, V.; Tait, P.; Wilcock, M.; et al.
<x xml:space="preserve">Abstract</x> In this study, we analyze the outcomes of transplant renal artery stenosis (TRAS), determine the different anatomical positions of TRAS, and establish cardiovascular and immunological risk factors associated with its development. One hundred thirty‐seven of 999 (13.7%) patients had TRAS diagnosed by angiography; 119/137 (86.9%) were treated with angioplasty, of which 113/137 (82.5%) were stented. Allograft survival in the TRAS+ intervention, TRAS+ nonintervention and TRAS− groups was 80.4%, 71.3% and 83.1%, respectively. There was no difference in allograft survival between the TRAS+ intervention and TRAS− groups, p = 0.12; there was a difference in allograft survival between the TRAS− and TRAS+ nonintervention groups, p < 0.001, and between the TRAS+ intervention and TRAS+ nonintervention groups, p = 0.037. TRAS developed at the anastomosis, within a bend/kink or distally. Anastomotic TRAS developed in living donor recipients; postanastomotic TRAS (TRAS‐P) developed in diabetic and older patients who received grafts from deceased, older donors. Compared with the TRAS− group, patients with TRAS‐P were more likely to have had rejection with arteritis, odds ratio (OR): 4.83 (1.47–15.87), p = 0.0095, and capillaritis, OR: 3.03 (1.10–8.36), p = 0.033. Patients with TRAS‐P were more likely to have developed de novo class II DSA compared with TRAS− patients hazard ratio: 4.41 (2.0–9.73), p < 0.001. TRAS is a heterogeneous condition with TRAS‐P having both alloimmune and traditional cardiovascular risk factors.